THE AFFECTION OF DETERMINANT EFFECT ON EMPLOYEE PERFORMANCE - Della Maya Puspita; Fauzi, Akhmad; Ika Korika Swasti (PT Larva Wijaya Penerbit, 2025)
The availability of qualified human resources in an agency or company will support optimal work results and the achievement of the company's vision and mission. One of the factors that need to be considered to keep employee performance at its maximum is to implement a work-life balance and a good work environment. This study aims to find out how work-life balance and work environment can affect employee performance with job satisfaction as a mediating variable. The research method used is quantitative with the Structural Equation Modeling-Partial Least Square (Sem-PLS) analysis technique. The variables studied in this study are work life balance (X1), work environment (X2), performance (Y), and job satisfaction (Z). The object of this study is an employee of Bank X in Sidoarjo. The sampling technique in this study is a saturated sampling technique or census. The number of samples in this study is 58 employees of Bank X in Sidoarjo. The results of the study showed that: work-life balance did not contribute to improving performance, the work environment contributed positively and significantly to improving performance, job satisfaction successfully mediated the influence of work-life balance on performance, the work environment did not contribute to improving performance through job satisfaction, job satisfaction also contributed positively and significantly to the improvement of the performance of Bank X employees in Sidoarjo.